EARNINGS RESPONSE COEFFICIENT: ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Suardana, Ketut Alit; Dharmadiaksa, Ida Bagus (Program Studi Akuntansi Fakultas Ekonomi Universitas Mahasaraswati Denpasar, 2018)
This study aims to analyze the effect of systematic risk, growth opportunities, leverage and firm size on earnings quality as measured by ERC. The population in this research is all manufacturing companies listed in BEI period 2011-2015. The type of data used is quantitative data and sourced from secondary data. The method of determining the sample using non-probability sampling method. Sample selection by purposive sampling technique. Data analysis technique used is multiple linear regression analysis. Based on the analysis, this study proves that systematic risk negatively affect on ERC, growth opportunities have positive effect on ERC, leverage have negative effect on ERC, and firm size has no effect on ERC.